DYNAMIC RISK AND NATURE BASED SOLUTION-BASED URBAN CONTROL 2022-2042 FOR POTENTIAL FLASH FLOOD BATU CITY - Dhirgantara Putra, Dekka
Currently hydrometeorological disasters show an increasing trend. The flash flood disaster is part of a hydrometeorological disaster which has indicated a significant impact on life and property. The main factor of flash floods is triggered by extreme rain intensity. Then related to the occurrence of landslides that clog the flow of the river to form a natural dam. To overcome the flash flood disaster, several countermeasures can be taken, namely by warning of hazard areas, early warning systems, community preparedness, and hydrometeorological forecasting. These countermeasures, only several areas that have the potential for flash floods are ready for this effort. One of the hydrometeorological disasters that occurred in Indonesia was the Banjir Bandang in Batu City. Flash floods in Batu City had an impact on 6 points, including: Bumiaji District, floods occurred in Bulukerto Village, Sumber Brantas Village and Punten Village. In Bulukerto Village there are two points. Namely in Sambong Hamlet and Beru Hamlet. Meanwhile in Batu District, flash floods occurred on Jalan Raya Dieng (Sidomulyo Village) and Jalan Raya Selecta (Tulungrejo Village). Based on the recorded disaster events, flash floods in Batu City have only occurred once, but it has had quite a large impact, because there are many residents' houses in Junrejo District. Based on the losses caused by the issue of this problem, it can be the basis for efforts to control the spatial pattern utilization of Batu City in the future. From the issue of hydrometeorological disaster problems in Batu City, it is the basis for the need for studies related to the study of the dynamics of flood hazard risk in the Spatio Temporal 2022-2042 perspective which can predict the effects of climate change and the meteorological disaster of flash floods in Batu City, as well as the value of the damage caused by the flash floods, with using the cellular automata method as a prediction of future land to see changes in the dynamics of vulnerability, then calculating risk based on a spatio-temporal perspective and how to control it with the Urban-Run Off Flow method combined with a Nature Based Solution Concept Direction in the Brantas River Basin in Batu City.